Molecular characterization and haplotypes of sheep and goat isolates of Cysticercus tenuicollis in Turkey - Kilinc, Seyma Gunyakti; Kesik, Harun Kaya; Simsek, Sami (Cambridge Univ Press, 2019)
Taenia hydatigena, is a common parasite, lived mostly in dogs and wild carnivores in its mature stage, and the larvae, Cysticercus tenuicollis, is found on ruminants and pigs. The aim of the current study was to determine the genetic diversity in 20 isolates of the sheep and goats. After the isolation of total genomic DNA from C. tenuicollis isolates, genetic characterization of the mitochondrial NADH dehydrogenase subunit 1 gene region was amplified using specific JB11-JB12 primers in PCR and the PCR products were sequenced and haplotype and genetic diversity analyses were utilized. As a result, multiple nucleotide changes were determined in the sequence analyses of the isolates leading to detection of 16 and 15 different haplotypes in sheep and goat samples, respectively. These findings are important in terms of showing the diversity of nucleotide variation in C. tenuicollis in Turkey.
Keywords: Cysticercus tenuicollis; goat; haplotype; sheep; Turkey